2008
DOI: 10.1103/physreva.77.043814
|View full text |Cite
|
Sign up to set email alerts
|

Filamentation in Kerr media from pulsed Bessel beams

Abstract: In contrast with filamentation of ultrashort laser pulses with standard Gaussian beams in Kerr media, three different types of Bessel filaments are obtained in air or in water by focusing ultrashort laser pulses with an axicon. We thoroughly investigate the different regimes and show that the beam reshapes as a nonlinear Bessel beam which establishes a conical energy flux from the low intensity tails toward the high intensity peak. This flux efficiently sustains a high contrast long-distance propagation and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 58 publications
5
128
0
6
Order By: Relevance
“…The central channel becomes larger with the fluence clamped at the level of 0.6 J/cm 2 corresponding to an intensity of 2.2 TW/cm 2 . These values are typical for filamentary propagation [13]. The pulse energy is therefore deposited in this larger area with a diameter of 15 µm [ Fig.…”
Section: Energy Depositionmentioning
confidence: 95%
See 1 more Smart Citation
“…The central channel becomes larger with the fluence clamped at the level of 0.6 J/cm 2 corresponding to an intensity of 2.2 TW/cm 2 . These values are typical for filamentary propagation [13]. The pulse energy is therefore deposited in this larger area with a diameter of 15 µm [ Fig.…”
Section: Energy Depositionmentioning
confidence: 95%
“…A crucial point when it comes to applications is that these non-diffractive beams have to keep their structure in the presence of the highly nonlinear propagation effects, so that energy is deposited along their whole length [13]. In order to produce extending Bessel beams, hundreds of microns long, conical angles of 10 • <θ B <20 • are employed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, long cylindrical micro-channels with high aspect ratios [8,9] up to 1200 have been demonstrated with singleshot ultrafast pulsed Bessel beams. The previous study with Bessel beam of variable pulse duration [10] also suggested that ps pulses are more beneficial for high efficiency energy deposition and could avoid temporal dynamics effects [11,12] which can compromise the stationarity of the Bessel beam propagation. Bhuyan et al [13] demonstrated that rear-side ablation under water immersion is a good strategy to facilitate debris evacuation and for obtaining taper-free micro/nano channel fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The self-reconstruction properties of filaments and their extension were also explained in terms of the energy reservoir surrounding filaments. 16 Nonlinear dynamics of pulsed Bessel beams [17][18][19] and possible applications [20][21][22] were also investigated.…”
Section: Introductionmentioning
confidence: 99%